Experimental Characterization of the Fatigue Life of Bolted Flange Connections in Wind Turbine Towers: Implications for Structural Integrity - Isik, Nisanur; Alemdar, Fatih (LATIN AMER J SOLIDS STRUCTURES, 2026)
The experimental study investigates design parameters affecting the fatigue performance of bolted flange connections using accelerated laboratory tests at 60-70% of static capacity. Constant-amplitude loading R = 2 Hz was applied to large-diameter high-strength bolts (M36 and M39, Grade 8.8), considering variations in flange material S355 and SAE 1045, bolt size, and loading 5 mm eccentricity. M39 bolts showed statistically significant longer fatigue life than M36 bolts 8,579 vs. 5,395 cycles, p = 0.023. A 5 mm loading eccentricity reduced fatigue performance due to induced bending effects. While both flange materials showed comparable fatigue lives, the higher ductility of S355 provided improved damage progression control. Dynamic stiffness monitoring identified a three-stage degradation process, with critical reductions in final fatigue stages, indicating potential for early failure detection. Although accelerated tests do not predict absolute service life, results provide relative performance rankings and practical guidance for bolt selection and design of large-scale bolted structures, particularly wind turbine towers.
Keywords: Bolted flange connections; fatigue; load eccentricity; dynamic stiffness; HIGH-STRENGTH BOLTS; PRESSURE DISTRIBUTION; GRID STRUCTURES; PERFORMANCE; JOINTS; Engineering; Mechanics